2021
DOI: 10.2147/prbm.s342155
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Psychosocial Factors and Adherence to Treatment in Men, Premenopausal and Menopausal Women with Type 2 Diabetes Mellitus

Abstract: Introduction Type 2 Diabetes Mellitus (T2DM) is a chronic disease that begins in adulthood, and is caused by multiple factors. The onset of menopause involves changes that predispose women to the development of T2DM, which can worsen if the adherence to treatment is inadequate due to psychosocial factors or medications. The present study aims to describe the psychosocial factors that may affect adherence to treatment among men and premenopausal and menopausal women with T2DM. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…[10][11][12] Additionally, the influence of hormonal factors and psychosocial aspects unique to females could impact medication adherence. [13][14][15][16] The study also examined the impact of various patient characteristics on DAPT noncompliance. Comorbidities played a significant role, with diabetes and chronic kidney disease showing a positive association with noncompliance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12] Additionally, the influence of hormonal factors and psychosocial aspects unique to females could impact medication adherence. [13][14][15][16] The study also examined the impact of various patient characteristics on DAPT noncompliance. Comorbidities played a significant role, with diabetes and chronic kidney disease showing a positive association with noncompliance.…”
Section: Discussionmentioning
confidence: 99%
“…[10–12] Additionally, the influence of hormonal factors and psychosocial aspects unique to females could impact medication adherence. [13–16]…”
Section: Discussionmentioning
confidence: 99%
“…Which explains that patients with higher denial about their illness are not able to implement adherent behaviour to manage their health condition and improve their chronic illness outcome. But statistically significant correlation between resilience and adherent behaviour explains that patients with higher resilience can better implement adherent behaviour in their life which will contribute to better chronic illness outcome (Catalán, Crisóstomo, Santamaría, Sainz, Valverde, & Jaimes, 2022;Escobar Florez, Aquilera, De la Roca-Chiapas, Cervantes, & Garay-Sevilla, 2021;White et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Health Attitudes and Behavior Several studies have been performed to evaluate attitudes of denial in patients with diabetes [76][77][78][79][80][81][82]. In particular, Hyphantis et al [77] showed that illness denial was a significant predictor of poor adherence (defined as delayed engagement to treatment) in outpatients with type 2 diabetes.…”
Section: Diabetology and Endocrinologymentioning
confidence: 99%